Gamification in Ecommerce - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (Research Parks Publishing LLC, 2023)
By nature, gamification thrives in the context of competition to win. Autonomy, rewards, participation, contest, and absorption play an essential role in its success. Gamification is the most entertaining technique to consider in engaging customers in the ever-evolving world of e-commerce. Ecommerce gamification is the technique for integrating game elements into your marketing strategy with the intention of entertaining users and influencing their behavior. This strategy is changing the way we shop in ecommerce and has many advantages, both for the shoppers and the stores. This paper provides an overview on gamification ecommerce with examples.